DNA replication dynamics of vole genome and its epigenetic regulation - Kathrin S. Heinz; Alexander Rapp; Corella S. Casas-Delucchi; Anne Lehmkuhl; Ismael Romero-Fernández; Antonio Sánchez; Oliver H. Krämer; J. Alberto Marchal; M. Cristina Cardoso (Epigenetics & Chromatin, 2019)
Abstract Background The genome of some vole rodents exhibit large blocks of heterochromatin coupled to their sex chromosomes. The DNA composition and transcriptional activity of these heterochromatin blocks have been studied, but little is known about their DNA replication dynamics and epigenetic composition. Results Here, we show prominent epigenetic marks of the heterochromatic blocks in the giant sex chromosomes of female Microtus cabrerae cells. While the X chromosomes are hypoacetylated and cytosine hypomethylated, they are either enriched for macroH2A and H3K27me3 typical for facultative heterochromatin or for H3K9me3 and HP1 beta typical for constitutive heterochromatin. Using pulse-chase replication labeling and time-lapse microscopy, we found that the heterochromatic block enriched for macroH2A/H3K27me3 of the X chromosome is replicated during mid-S-phase, prior to the heterochromatic block enriched for H3K9me3/HP1 beta, which is replicated during late S-phase. To test whether histone acetylation level regulates its replication dynamics, we induced either global hyperacetylation by pharmacological inhibition or by targeting a histone acetyltransferase to the heterochromatic region of the X chromosomes. Our data reveal that histone acetylation level affects DNA replication dynamics of the sex chromosomes’ heterochromatin and leads to a global reduction in replication fork rate genome wide. Conclusions In conclusion, we mapped major epigenetic modifications controlling the structure of the sex chromosome-associated heterochromatin and demonstrated the occurrence of differences in the molecular mechanisms controlling the replication timing of the heterochromatic blocks at the sex chromosomes in female Microtus cabrerae cells. Furthermore, we highlighted a conserved role of histone acetylation level on replication dynamics across mammalian species.